Isolation of microorganism from oil palm sap - Nurul Nadia Ummira, Abu Bakar (2011)
The oil palm sap is come from the oil palm trunk. The outer of the trunk is being process to become plywood but for the most moisture part, it has been squeezed in order to get the sap. The unfermented sap is clean, sweet, colorless syrup containing about 10–12 % sugar, which is mainly. Sap also rich with other simple sugar such as glucose, fructose, raffinose, amino acid, vitamins and other essential nutrients. This research is aim to isolate bacteria using streaking plate method from palm oil sap and identified by using Bergey‟s manual. . A total of 15 colonies were successfully isolated from the palm oil sap. From analysis, Lactobacillus spp. was the dominant species isolated followed by Pseudomonas spp., Corynebacterium spp and Vibro spp. For the kinetic growth study, the kinetic values that need to determine are maximum growth rate (µ), decay coefficient (K), yield coefficient (Y) and substrate coefficient (Ksmd). The growth kinetic is calculated by measured the substrate concentration and biomass weight. Kwas determined to be 0.034 hd -1 and Y as 0.124 g/L. Meanwhile, µm was 0.2532 h-1 and K was 536.4557 g/L. As a conclusion, it is well known that the environment condition influence the bacteria species and growth activities of bacteria.